The Adaptability and Effectiveness of the Principals' Leadership Styles in Building Religious Tolerance at Senior High Schools in Manado City - Meyke Machrita Mamahit (Sekolah Tinggi Agama Kristen Terpadu Pesat, 2023)
The quality of the school depends on how well the principal utilizes the sources in the school and adapts his leadership styles, which were applied effectively and efficiently to achieve the school's goal. Nowadays the school more focuses on the increasing of students' academics, less giving attention to the development of students' religious attitude and behavior so that the brawl happened out of school. The role of principal and teacher is very important in forming the religious attitude and behavior of students. The principal's leadership style which is adapted with the situation and the need of all members of school in building religious tolerance can create the harmonious situation in achieving the school's goal. This research aimed to describe and analyze the adaptability and effectiveness of the principals' leadership styles in building religious tolerance at Senior High Schools State in Manado City. The approach utilized mixed methods: quantitative and qualitative approaches with descriptive methods. The research findings showed that the adaptability and effectiveness of the principals' leadership styles in building religious tolerance at Senior High Schools State in Manado City were adaptable and effective. The conclusion was that the leadership styles applied by the principals at Senior High Schools State in Manado City in building religious tolerance were adaptable and effective to the situation, the need of teachers, staff, and students to run the religion activities in school according to their faith and beliefs. It was recommended that the principals increase the adaptability and effectiveness of their leadership styles to build the religious tolerance in schools harmoniously. Abstrak Kualitas sekolah bergantung pada seberapa baik kepala sekolah memanfaatkan sumber daya sekolah dan mengadaptasikan gaya kepemimpinan yang diterapkan secara efektif dan efisien untuk mencapai tujuan sekolah. Saat ini sekolah lebih terfokus pada peningkatan akademik peserta didik, kurang memberi perhatian pada perkembangan sikap dan perilaku religius peserta didik sehingga terjadi tawuran di luar sekolah. Peran kepala sekolah dan guru sangat  penting dalam membentuk sikap dan perilaku religius peserta didik. Gaya kepemimpinan kepala sekolah yang diadaptasikan dengan situasi dan kebutuhan semua warga sekolah dalam membangun toleransi beragama dapat menciptakan situasi yang harmonis dalam  mencapai tujuan sekolah. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis keadaptabilitasan dan keefektifan gaya kepemimpinan kepala sekolah dalam membangun toleransi beragama di SMA Negeri Kota Manado. Pendekatan yang digunakan metode campuran: pendekatan kuantitatif dan kualitatif dengan metode deskriptif. Hasil penelitian adalah keadaptabilitasan dan keefektifan gaya kepemimpinan kepala sekolah dalam membangun toleransi beragama di SMA Negeri Kota Manado adalah adaptif dan efektif. Kesimpulannya adalah gaya kepemimpinan yang diterapkan kepala sekolah di SMA Negeri Kota Manado dalam membangun toleransi beragama adalah adaptif dan efektif terhadap situasi, kebutuhan guru, staf dan siswa untuk menjalankan kegiatan keagamaan di sekolah menurut iman dan kepercayaan mereka. Direkomendasikan agar kepala sekolah    meningkatkan keadaptabilitasan dan keefektifan gaya kepemimpinan dalam membangun toleransi beragama di sekolah demi terciptanya keharmonisan.